1993
DOI: 10.1038/362638a0
|View full text |Cite
|
Sign up to set email alerts
|

Radial mosaicism and tangential cell dispersion both contribute to mouse neocortical development

Abstract: The mammalian neocortex is generated by waves of migrating cells originating from the ventricular zone. Radial migration along radial glia has been proposed as the dominant mechanism for this process. The radial unit hypothesis is poorly supported by retroviral lineage studies, however, and although some clones show limited radial organization, the emphasis appears to be on widespread tangential dispersion. Here we investigate the pattern of cortical cell dispersion using transgenic mice in which roughly half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
1
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(93 citation statements)
references
References 18 publications
8
82
1
2
Order By: Relevance
“…Initial efforts to test the hypothesis, in which retroviral labeling was used to mark and visualize clones of neurons in the developing neocortex, failed to provide support for this model, instead finding evidence for both horizontal and radial clones of cells (Price and Thurlow 1988;Walsh and Cepko 1992;Walsh and Cepko 1993). However, after some debate, subsequent studies of the subcortical origins of inhibitory interneurons of the cortex and further lineage analyses confirmed the accuracy of the radial unit hypothesis (Tan and Breen 1993;Soriano et al 1995;Anderson et al 1997). These studies revealed that the glutamergic neuronal progeny of neocortical stem cells form radial columns that span the cortical plate (Tan and Breen 1993;Soriano et al 1995) (Fig 2C).…”
Section: Development Of the Neocortex-the Radial Unit Hypothesismentioning
confidence: 95%
“…Initial efforts to test the hypothesis, in which retroviral labeling was used to mark and visualize clones of neurons in the developing neocortex, failed to provide support for this model, instead finding evidence for both horizontal and radial clones of cells (Price and Thurlow 1988;Walsh and Cepko 1992;Walsh and Cepko 1993). However, after some debate, subsequent studies of the subcortical origins of inhibitory interneurons of the cortex and further lineage analyses confirmed the accuracy of the radial unit hypothesis (Tan and Breen 1993;Soriano et al 1995;Anderson et al 1997). These studies revealed that the glutamergic neuronal progeny of neocortical stem cells form radial columns that span the cortical plate (Tan and Breen 1993;Soriano et al 1995) (Fig 2C).…”
Section: Development Of the Neocortex-the Radial Unit Hypothesismentioning
confidence: 95%
“…In the past, it was generally believed that soon after leaving the cell cycle a neuron would migrate outward to its final destination in the telencephalon along radial glial processes (Rakic, 1972;McConnell, 1988;Misson et al, 199 la,b). Recent studies using lineage tracers have questioned whether all cells departing the telencephalic ventricular zone migrate radially Cepko, 1992, 1993;Grove et al, 1993;Tan and Breen, 1993). Moreover, studies utilizing organotypic cultures and time-lapse videomicroscopy have presented direct evidence of tangential dispersion of migratory cells within the intermediate zone (O'Rourke et al, 1992) or of cells within the ventricular zone (Fishell et al, 1993).…”
Section: Expression Of Neuron-specific Tubulin Defines a Novel Populamentioning
confidence: 99%
“…Female mice that carry a marker transgene on the X chromosome, which is subject to random X-inactivation, may produce mosaic patterns of transgene activity that also allow investigation of cell lineages (Tan and Breen, 1993).…”
Section: Introductionmentioning
confidence: 99%